The Impact of Budget, Accountability Mechanisms and Renewable Energy Consumption on Environmentally Sustainable Development: Evidence from Indonesia - Pattiruhu, Jozef R. (International Journal of Energy Economics and Policy, 2020)
The goal linked with the current article is to analyse the impact of the budget approved for environmental development, accountability mechanism of the government and renewable energy consumption on the environmental sustainability development of Indonesia. The quantitative method has been executed through which secondary data has been extracted from the database of World Bank along with the finance ministry of Indonesia from 1985 to 2017 while for the analysis purpose ARDL approach has been used. The results revealed that positive nexus among the budget approved for environmental development, accountability mechanism of the government, renewable energy consumption and environmental sustainability development of Indonesia in both the short and long run. The results also revealed that negative linkage among the energy import and environmental sustainability development of Indonesia. These findings provided suitable measures to the regulatory authority of the country that they should approve more budget for environmental development along with maintaining the high accountability mechanism that enhances the environmental sustainability development in Indonesia. Keywords: Environmental development, Accountability mechanism, Renewable energy consumption, Environmental sustainability development JEL Classifications: F64, O13, P18 DOI: https://doi.org/10.32479/ijeep.10624